A parametric model for estimating force of infection for hepatitis B-case study Komfo Anokye Teaching Hospital - Opoku-Addo, Emmanuel Kwame (2021)
A thesis submitted to the Department of Mathematics, Kwame Nkrumah University of Science and Technology, in partial fulfillment of the requirement for the degree of Msc. Applied Statistics